Death and taphonomy of Holocene stromatolites from Lagoa Vermelha, Brazil - Keim, Carolina Neumann; Farina, Marcos (Comptes Rendus. Géoscience, 2023)
Stromatolites are laminated rocks, comprising both authigenic and allochthonous materials, which arise under strong influence of both microorganisms and environmental conditions. Growing stromatolites are rare nowadays, limiting our understanding on how microbial mats produce stromatolites. Stromatolites from Lagoa Vermelha in Brazil were claimed as living, lithifying structures several years ago, but recently have been reported as dead, bleached skeletons. Here we confirm that they are currently not forming new laminae. This was confirmed by the absence of the microbial mat coat, enabling colonization of exposed surfaces by barnacles, boring cyanobacteria, and burrowing metazoans, which contributed to erosion and loss of some original features while adding new, distinct biomarkers.